δ18O OF TREE-RING CELLULOSE IN TWO SPECIES (SPRUCE AND OAK) AS PROXIES OF PRECIPITATION AMOUNT AND RELATIVE HUMIDITY IN NORTHERN JAPAN - Tsuji H.; Nakatsuka T.; Takagi K. (My University, 2006)
Relationships between climatic factors and δ18O values of tree rings in two species with different root systems were investigated in the northern area in Hokkaido Island, northern Japan. This region has a heavy snow cover in winter and has a humid climate throughout the year. In the case of spruce (Picea jezoensis), which has shallow roots, the δ18O values are negatively correlated with precipitation in July and August, probably due to higher relative humidity in summer and lower δ18O of summer precipitation in a year of higher summer precipitation, which is governed by the precipitation amount effect. Thus, the δ18O value of tree-ring cellulose in spruce must be valuable as a proxy of summer precipitation in this area. On the other hand, the δ18O value in oak (Quercus crispula), which has deeper roots than spruce, is not very sensitive to summer precipitation, but is negatively correlated mainly with relative humidity in July and August; this can be attributed to the smaller 18O enrichment in leaf water in the summer of higher relative humidity. Our results indicate that δ18O values of tree rings in two species with different root systems from the same forest have the potential to reconstruct the two different climate factors. © 2006 Elsevier B.V. All rights reserved.
Keywords: δ18O; OAK; PRECIPITATION; RELATIVE HUMIDITY; ROOT; SPRUCE; TREE RINGS